The role of demographic factors of owners managers on small and medium enterprises (SMEs) performance in Yobe State Nigeria - Zannah, Mohammed; Mahat, Fauziah; Ariffin, Bany; Ali, Noor Azman (Globeedu Group, 2017)
Small and Medium Enterprise are an engine for the economic growth and development of every country of the world, the sector experiencing great failure over the years which make it compulsory to entrepreneurs, researchers and government authorities to give attention to curb the issue. This study investigates the effect of demographic factors of owner’s managers on Performance of Small and Medium enterprises in Yobe state, despite the fact that there is limit research done on the demographic factor by previous researchers. This research used the quantitative approach with a descriptive survey of 110 samples using Cochran sampling technique. The questionnaires were tested using Spss to make sure it is reliable and the Spss result shows it were reliable with Cronbach alpha of .82. The finding of the study determined best on the proposed hypotheses and the analysis result indicates all the variable have a positive and significant relationship with the SMEs Performance.